1998
DOI: 10.1159/000028433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speaking Style on a Locus Equation Characterization of Stop Place of Articulation

Abstract: Locus equations were employed to assess the phonetic stability and distinctiveness of stop place categories in reduced speech. Twenty-two speakers produced stop consonant + vowel utterances in citation and spontaneous speech. Coarticulatory increases in hypoarticulated speech were documented only for /dV/ and [gV] productions in front vowel contexts. Coarticulatory extents for /bV/ and [gV] in back vowel contexts remained stable across style changes. Discriminant analyses showed equivalent levels of correct cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In speech, several studies have looked for invariants, either in the extrinsic acoustic domain (Stevens & Blumstein, 1978;Strange et al, 1983;Sussman et al, 1998), or in the intrinsic domain (Fujimura, 1986;Boë et al, 1992;Tremblay et al, 2003;Baer et al, 1988;Maeda & Honda, 1994). Analogously to what force-fields do for limb movement, perturbation paradigms have been elaborated to break down the usual associations between extrinsic (acoustics) and intrinsic (articulation) variables.…”
Section: Extrinsic Versus Intrinsic Motor Goals In Speech Productionmentioning
confidence: 99%
“…In speech, several studies have looked for invariants, either in the extrinsic acoustic domain (Stevens & Blumstein, 1978;Strange et al, 1983;Sussman et al, 1998), or in the intrinsic domain (Fujimura, 1986;Boë et al, 1992;Tremblay et al, 2003;Baer et al, 1988;Maeda & Honda, 1994). Analogously to what force-fields do for limb movement, perturbation paradigms have been elaborated to break down the usual associations between extrinsic (acoustics) and intrinsic (articulation) variables.…”
Section: Extrinsic Versus Intrinsic Motor Goals In Speech Productionmentioning
confidence: 99%
“…For example, slopes for the bilabial plosives such as /b/ are consistently steeper and corresponding y-intercepts, lower, compared to those observed for the alveolar cognate /d/ (e.g. Fowler 1994, McLeod et al 2001, Sussman, Bessell, Dalston & Majors 1997, Sussman, Dalston & Gumbert 1998. These observations suggest that /b/ in CV sequences has the highest levels of coarticulation with the ensuing vowel, and therefore the lowest levels of articulatory resistance due to the independence between the main articulators involved in the production of /bV/; the lips and the lingual system.…”
Section: Temporal and Spectro-temporal Measures Of Speechmentioning
confidence: 93%
“…For a particular phonetic class c, the joint probabilities of the phonetic-class dependent UBMs are determined by: (8) where c ∈ {1, . .…”
Section: B Phonetic-class Dependent Ubmsmentioning
confidence: 99%
“…For example, studies in speech prosody have shown that individual speakers exhibit substantial differences in voluntary speaking behaviors such as lexicon, prosody, intonation, pitch range, and pronunciation [6], [7]. Studies in linguistics have shown that speaking styles have significant effect on pronunciation patterns [8]. Kuehn and Moll [9] measured the velocity and displacement of the tongue during speech production and found appreciable variation of these two measurements among different speakers.…”
Section: Introductionmentioning
confidence: 99%